1988
DOI: 10.1093/nar/16.7.2805
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory region of the human plasminogen activator inhibitor type-1 (PAI-1) gene

Abstract: The human gene for plasminogen activator inhibitor type-1 (PAI-1) has been isolated and its promoter region characterized. PAI-1 regulation by glucocorticoids, transforming growth factor-beta (TGF-beta) and the phorbol ester PMA is shown to be exerted at the promoter level. A fragment spanning 805 nucleotides of the 5' flanking and 72 of the 5' untranslated region contain information enough to promote transcription and to respond to glucocorticoids when fused to a reporter gene and transfected into human fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…9b). Although the PAI-1 promoter used in this study contained TGFb1 responsive elements (Riccio et al 1988(Riccio et al , 1992, it did not appear to have a DRE (GCGTG) motif to bind the AhR/Arnt complex. However, the gene for prostaglandin endoperoxide H synthase-2 was also induced by TCDD in a DRE-independent fashion with c-Src-mediated activation but still in an AhR-dependent manner (Vogel et al 2000).…”
Section: Discussionmentioning
confidence: 93%
“…9b). Although the PAI-1 promoter used in this study contained TGFb1 responsive elements (Riccio et al 1988(Riccio et al , 1992, it did not appear to have a DRE (GCGTG) motif to bind the AhR/Arnt complex. However, the gene for prostaglandin endoperoxide H synthase-2 was also induced by TCDD in a DRE-independent fashion with c-Src-mediated activation but still in an AhR-dependent manner (Vogel et al 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Comparison of 5%-flanking regions revealed two highly conserved elements with \80% identity in the proximal promoter (at −90 to − 25) and in a distal sequence (at −753 to − 512). The common features detected in the 5%-flanking regions of the PAI-1 genes of these three species are a consensus TATA box and sequences closely related to PEA3, AP1, CTF/NF-1, and Sp1 recognition sites [268][269][270]. The 5%-flanking region of the human PAI-1 gene contains four putative AP1-binding sites: −58 to −50 (TGAGTTCA), − 79 to − 72 (TGAGTGG), −662 to −656 (TGTATCA) and −721 to −714 (TGA-CACA), although none is identical to the consensus AP1 site [TGA(G/C)TCA] to which c-Fos/c-Jun heterodimers preferentially bind.…”
Section: The Tpa Genementioning
confidence: 99%
“…The human PAI-1 promoter contains sequence stretches closely related to recognition sites for PEA3, AP1, AP2, Sp1, CTF/NF1, and Smad as well as cAMP and glucocorticoid-responsive elements (24,25). However, perfect consensus motifs for Rel protein binding are missing.…”
Section: Stable Overexpression Of ␣ V ␤ 3 In Human Ovarian Cancer Celmentioning
confidence: 99%
“…In earlier studies we have demonstrated that Rel proteins substantially contribute to elevated uPA gene expression in human ovarian cancer cells, thereby promoting the multiple functions of uPA during tumor growth and metastasis (22,23). The human PAI-1 promoter contains recognition sites for transcription factors including PEA3, AP1, AP2, and Sp1, whereas perfect consensus motifs for the binding of Rel proteins are lacking (24,25).…”
mentioning
confidence: 99%